The post-war reconstruction of waqf properties in Marawi City: Prospect and challenges - Tagoranao, Mariam S.; Gamon, Alizaman Dumangcag (Academy of Contemporary Islamic Studies (ACIS) UiTM, 2017)
It was the five months Marawi sieged between the Philippine Armed Forces and the ISIS group that brought the masjid and madrasah and other waqf properties into ruins and ashes. The government promised to reconstruct the city, but there is no guarantee that waqf properties will be included in the proposed transformation plan on the ground that these are not constitutionally considered as part of the government assets. It will be the responsibility of the people in Marawi City and the religious organizations to work together and find ways to reconstruct and revive the destroyed masjid, madrasah, waqf buildings and other related properties. The aim of this paper is to identify the prospect and challenges in reviving and reconstructing the waqf properties, including the waqf lands claimed by the government as part of the military reservation. The importance of waqf properties for the socio-economic development of Muslims who were victims of the war will be highlighted. The rights and rule of law, as well as the strategies in the reconstruction of masjid and madrasah, will be examined. This study will use qualitative research method to be gained from library research, and web-based journals and articles. The finding will show that the reconstruction of the waqf properties will take many years, unless, the government and other Muslim countries will provide financial assistance and services knowing the important role of these properties to the socio-economic development of the Muslim population of Marawi City.